Pengaruh Profitabilitas terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Moderasi pada Perusahaan yang Terdaftar Di Index LQ45 Periode 2019-2022 - Abdilah, Agustini; Prijanto, Budi (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2024)
Currently, the world has entered the era of globalization with economic threats, the challenges faced by companies are becoming increasingly severe, this will have an impact on tight competition for companies. Therefore, companies will compete to attract the attention of investors in order to survive, one way is by increasing the value of the company. Company value is one of the capital market indicators in assessing the company as a whole, where the company value shows its future prospects. This research aims to determine and analyze the influence of profitability on company value and whether dividend policy is able to moderate (strengthen/weaken) the relationship between profitability and company value, to be used as a benchmark for companies regarding the most significant factors in increasing company value. The type of data used is secondary quantitative data in the form of annual financial reports of companies listed on the LQ45 Index for the 2019-2022 period. The sample in this study was 10 companies listed on the LQ45 Index for the 2019-2022 period, using a purposive sampling method. The data analysis technique in the research uses Moderated Regression Analysis (MRA) using the SPSS For Windows 26.0 software tool. The research results show that profitability has a significant effect on company value and dividend policy is able to moderate (strengthen) the relationship between profitability and company value.